2007
DOI: 10.1093/humrep/dem373
|View full text |Cite
|
Sign up to set email alerts
|

Detection of zona pellucida proteins during human folliculogenesis

Abstract: BACKGROUND: The stage of folliculogenesis at which the human zona pellucida (ZP) is initiated and the cells responsible for the origin of the ZP continue to be controversial. This study characterizes the development of the ZP during human folliculogenesis using ovarian samples donated from patients requesting ovarian storage. METHODS: Follicles (from n 5 18 patients, 14-40 years old) within fresh tissue and following development in a xenograft system were stained, using immunohistochemical techniques, for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 45 publications
1
27
1
2
Order By: Relevance
“…In women, ZP1 and ZP3 are expressed in oocytes of most primordial follicles, whereas ZP2 is only detected in one third of primordial follicle oocytes although all three proteins are detected in cuboidal granulosa cells (50). Only ZP1 and ZP3 have been previously reported (51) in human fetal ovaries, and whereas expression of ZP1 was low, ZP3 was present at 11 wk and strongly present in oocytes from 17 wk onward.…”
Section: Zona Pellucida Genesmentioning
confidence: 83%
“…In women, ZP1 and ZP3 are expressed in oocytes of most primordial follicles, whereas ZP2 is only detected in one third of primordial follicle oocytes although all three proteins are detected in cuboidal granulosa cells (50). Only ZP1 and ZP3 have been previously reported (51) in human fetal ovaries, and whereas expression of ZP1 was low, ZP3 was present at 11 wk and strongly present in oocytes from 17 wk onward.…”
Section: Zona Pellucida Genesmentioning
confidence: 83%
“…The human ZP is formed during early folliculogenesis, and consists of four glycoproteins (ZP1-ZP4) which are actively secreted by oocytes and granulosa cells that support the growth of ova (5,6). The ability of embryos to hatch from their ZP is recognized as one of the critical embryonic processes affecting the implantation rates in human assisted reproduction (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…Gook et al [13] have demonstrated that ZP protein levels increase in the cytoplasmic granulosa cells during follicular development. The presence of these ZP proteins has been also detected in primordial follicles during oogenesis.…”
Section: Discussionmentioning
confidence: 99%